The multiple intelligence: evaluation and relationship with the yield in mathematics in students of the fifth year of secondary of Lima Metropolitan - Aliaga T., Jaime (2012)
The theory of the Multiple Intelligence represents an innovative vision in the field of the psychology of the education, because it offers a different mark for the best alignment in the teaching-learning process, making possible that the student identifies his strong and weak intellectual points better; and that, with this information, the or the educational one selects the resources and didactic strategies so that in work group that it develops even more the strongest and improve the weak ones, always looking for the achievement of their personal satisfaction and professional success. In this perspective, the evaluation of the multiple intelligence in a valid and reliable way acquires fundamental importance, for what we decide to elaborate one when not existing in the country instruments with these characteristics; also, also interested in the problem of the first floor school yield in mathematics, to subject to contrast the hypothesis that the Intelligence Multiple Logical Mathematics will be related in a higher way that the other multiple intelligence with the school yield in mathematics, and more with this than with the general academic yield. The Questionnaire of Multiple Intelligence was elaborated (CUIM) based on the frame of Gardner, using stops to establish its psychometric properties a sample of 1291 people of both sexes, the fifth year-old students, university students and preuniversitarys with a resolved interest for the career to continue, and for painters and dancers. The hypothesis was contrasted in a second sample composed by 960 students the fifth years of secondary. The secondary students of both samples came from 14 educational institutions of state and private administration located in the diverse districts of Metropolitan Lima. The results indicate that the CUIM has psychometric characteristic of reliability and validity that endorse it as an appropriate instrument for the achievement of its purpose, and that the hypothesis is supported by the data.